(untitled) (Web of Teachers: Inderscience Research, 2023)
Applied linguistics has influenced or may influence in the future the teaching and learning of English as a foreign language. The observations in applied linguistics may help us to improve the methods of language teaching. The observation that can be done is by contrasting native language and target language. By contrasting the two languages we can find the similarities and differences. One kind of contrastive analysis is language interference. It is most commonly discussed in the context of English language learning and teaching, but it can occur in any situation when someone does not have a native-level command of a language, as when translating into a second language.